(untitled) - Katz, William A (Boston, 2002)
The book explains the essential reference processes and sources in today;s libraries. It is a tool for understanding and mastering fundamental reference forms - online, in print, and elsewhere. This eighth edition is completely rewritten to reflect the radical changes library science has undergone since the advent of widely available electronic databases and the Internet
Keywords: Reference services (Libraries),Reference books,Dịch vụ tra cứu (Thư viện),Sách tra cứu; Bibliography,Thư mục